THU0209 UPTAKE OF JANUS KINASE INHIBITORS FOR MANAGEMENT OF RHEUMATOID ARTHRITIS IN AUSTRALIA. (2nd June 2020) - Littlejohn, G.; Smith, T.; Tymms, K.; Youssef, P.; Cooley, H.; Ciciriello, S.; Mathers, D.; Griffiths, H.
Abstract : Background: JAK inhibitors (JAKi) are oral tsDMARDs with a different mode of action (MOA) to both oral cs- and parenteral bDMARDs. In Australia the cost of b/tsDMARDs for treatment of RA is subsidized if the patient has documented high levels of clinical/laboratory disease activity and has not responded to a pre-specified combination of csDMARDs, including MTX. Once eligible for subsidy the clinician can prescribe the b/tsDMARD deemed most clinically appropriate. Objectives: To determine the patterns of use and reasons for initiation and discontinuation of JAKi in real-world rheumatology practice in Australia. Methods: Deidentified clinical data were sourced from the OPAL dataset, which is collected in a custom-built electronic medical record at the time of the consultation 1 by 94 rheumatologists in Australia, representing one third of Australian clinical rheumatologists. Data from patients >18 years with a diagnosis of RA who commenced a b/tsDMARD between Jan-2007 and Sept-2019 were included in the analysis. Tableau ® was used to display data on medication initiation and cessation dates, and reasons for starting and stopping b/tsDMARDs, which is recorded at the time of the decision. Results: At Sept 2019, there were 45, 317 patients with RA in the data set, with 27% prescribed b/tsDMARDs. Of patients currently on treatment at Sept 2019, 53% were receiving a TNFi and 21% a JAKi, with the remainder receiving tocilizumab, abatacept or rituximab. Of patients who commenced their current treatment after JAKi's become available in Sept 2015, 46% were treated with a TNFi, and 32% were treated with a JAKi. Tofacitinib (TOF) has been the most prescribed b/tsDMARD since Sept 2015 with 22% of all initiations; however, since baricitinib (BARI) became available in Sept 2018, it has taken over as the preferred JAKi with 24% of new initiations compared to 14% for TOF. From Sept 2018-Sept 2019 etanercept and adalimumab were the most commonly prescribed agents in first line, followed by TOF then BARI; however, BARI was the most prescribed agent in lines 2-6+ (figure 1 ). The main clinician-listed reason for choice of TOF was MOA in 54%, efficacy compared with alternatives in 30%, mode of administration in 7%, efficacy as monotherapy in 7%, and safety in 1%. BARI was chosen for MOA in 35%, efficacy compared with alternatives in 38%, mode of administration in 12%, efficacy as monotherapy in 12%, and safety in 1%. The main reasons for stopping TOF were lack of efficacy (34%), better alternative (25%) and adverse reaction (13%); those for BARI were lack of efficacy (35%) and adverse reaction (25%) which is consistent with the rates observed in the first 12-months of clinical experience with TOF, and better alternative (12%). Patient non-adherence was listed in 1% and 2% of cessations for TOF and BARI, respectively. 45% of patients discontinuing a JAKi in first line switched to a TNFi in second line, and 40% switched to another JAKi, citing lack of efficacy, adverse reaction, and better alternative as the reason for switching. Conclusion: There has been significant and sustained uptake of JAKi for the management of RA in Australia. MOA and perceived efficacy rate much higher than mode of administration for clinicians when selecting a JAKi. Clinical outcomes and persistence following JAKi cycling requires further investigation. References: Littlejohn GO, Tymms KE, Smith T, Griffiths HT. Using big data from real-world Australian rheumatology encounters to enhance clinical care and research. Clin Exp Rheum Nov 2019 Disclosure of Interests: None declared